Аllergic Basal Deciduitis as a Reason of Recurrent Antenatal Fetal Death - Kamyshanskiy , Yevgeniy; Kostyleva, Olga; Tussupbekova, Maida; Stabayeva, Leila; Imanbayeva, Gulnazira; Nygyzbayeva, Raihan; Kotov, Evgeniy; Kossitsyn, Denis (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Allergic diseases of pregnant women are associated with chronic placental insufficiency and the development of immunopathological conditions of unknown etiology in a child in postnatal life. Pregnancy with bronchial asthma is often complicated by intrauterine growth retardation, preeclampsia, and antenatal fetal death. AIM: The objective was to present a clinical case of recurrent antenatal fetal death in the third trimester in women with bronchial asthma under controlled course. CASE REPORT: Pregnancy proceeded without clinical signs of exacerbation of bronchial asthma and allergic status. However, chronic inflammation with eosinophilia in the intervillous space and the basal lamina was revealed in the placenta tissue. Eosinophilia of the intervillous area was accompanied by obliteration of the intervillous area by fibrin deposits. CONCLUSION: We suppose that immunological inflammation at the fetoplacental unit level can occur regardless of the mother’s allergic status. Moreover, it is likely that the objective state of the mother in the presence of an allergic disease does not reflect the presence/absence of an immunological process in the placenta, as the immunological inflammatory process can develop in different compartments (at the level of the mother’s body and the placental-fetal compartment) with varying degrees of severity.